Antibacterial Effects of Er:YAG Laser Irradiation on Candida–Streptococcal Biofilms - Zuzanna Grzech-Leśniak; Jakub Pyrkosz; Jagoda Szwach; Patrycja Kosidło; Jacek Matys; Rafał Wiench; Magdalena Pajączkowska; Joanna Nowicka; Marzena Dominiak; Kinga Grzech-Leśniak (Life)
In contemporary dentistry, laser-based interventions have become one of the mainstays of care for patients with oral biofilm diseases, such as candidiasis, periodontal disease and peri-implantitis. The purpose of this study was to evaluate the effectiveness of Er:YAG laser (LightWalker, Ljubljana, Fotona, Slovenia) irradiation at varying irradiance levels (T1: 11.3 W/cm2 and T2: 120.54 W/cm2) on microbial viability in single- and dual-species biofilm models, focusing on Candida albicans, Candida glabrata and Streptococcus mutans, to address challenges in managing complex oral biofilms in clinically relevant settings. The results showed substantial microbial reduction, with C. albicans being the most susceptible microorganism (93–99.9%), while C. glabrata exhibited marked resistance at higher irradiance levels. Interestingly, S. mutans demonstrated varying reductions based on the biofilm composition, highlighting the influence of microbial interactions. This study concluded that the Er:YAG laser effectively reduced biofilm viability, with its efficacy depending on the microbial composition and irradiance settings. These findings highlight the need for tailored erbium laser parameters to optimize clinical outcomes, underscoring the need for individualized polymicrobial biofilm management, particularly in periodontal and peri-implant therapies.